2023
DOI: 10.2174/1567201819666220607153457
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Quality Evaluation of Honokiol Nanoparticles Using a New Polysaccharide Polymer as its Carrier

Abstract: Objective: To improve solubility of Honokiol (HNK), Honokiol nanoparticles (HNK-NPs) were prepared by using a new biodegradable polysaccharide polymer as its carrier. Methods: HNK-NPs were prepared by hydrophilic polymer coagulation method, and the processing parameters were optimized according to average particle size and PDI by single factor experiment. The morphology of the optimized nanoparticles was investigated by TEM and the in vitro release was carried out to evaluate the optimized HNK-NPs. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, earlier studies showed that HNK is a lipophilic polyphenol compound that exhibited poor tissue distribution and solubility when given directly; by encapsulating HNK into liposome-based nanoparticles, cellular availability, targeted tissue or cellular distribution can be optimized. [49][50][51][52] Our RNAseq analysis indicated that besides the known roles in regulating oxidative stress responses, genes related to spermatogenesis and sperm motility were also altered upon nHNK administration. We observed that upon nHNK treatment, a cell proliferation marker Ki67 and spermatogenesis marker KIF11 protein expression levels were upregulated and presented at the seminiferous tubules' outer layer where spermatogonium and primary spermatocyte locate, suggesting nHNK treatment promotes testicular cell proliferation and the subsequent restoration of spermatogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…However, earlier studies showed that HNK is a lipophilic polyphenol compound that exhibited poor tissue distribution and solubility when given directly; by encapsulating HNK into liposome-based nanoparticles, cellular availability, targeted tissue or cellular distribution can be optimized. [49][50][51][52] Our RNAseq analysis indicated that besides the known roles in regulating oxidative stress responses, genes related to spermatogenesis and sperm motility were also altered upon nHNK administration. We observed that upon nHNK treatment, a cell proliferation marker Ki67 and spermatogenesis marker KIF11 protein expression levels were upregulated and presented at the seminiferous tubules' outer layer where spermatogonium and primary spermatocyte locate, suggesting nHNK treatment promotes testicular cell proliferation and the subsequent restoration of spermatogenesis.…”
Section: Discussionmentioning
confidence: 85%
“…Weng et al formulated HNK-loaded nanoparticles using a novel biodegradable polysaccharide, HZ0223AP-PPT, as the carrier material. 74 These nanoparticles demonstrated excellent stability and safety, facilitating drug-controlled release in vitro.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%